Development length of Tension Bars in Concrete Beams- Revisited (Iraqi Journal of Civil Engineering, 2018)
Presently development length of tension bars in reinforced concrete beams, in both codes and researches has a very wide range on the influence of major parameters. Namely, the influence of concrete compressive strength f́c affects the development length of beams by varying power values: 1/2, and 1/3. It is well known that the development length of beams is essentially based on empirical or semi empirical formulae. A total of 254 NSC and HSC tested beams available from the literature are studied in this work. These includes 154 beams without transverse reinforcement and 100 with transverse reinforcement and having a different compressive strength ranged from (16.4 – 98) MPa. The best available design method obtained from the literature leads to 43.31% increase in the coefficients of variation COV compared to the proposed design method in this work, which is essentially whose COV of 14.06%.